Answer:
5
Step-by-step explanation:
Begin by removing the brackets.
5x + 5 - 5x
Notice that there are two 5xs. They are of opposite signs so they cancel
Answer 5
For this case we have the following equations:
2x - 3y = 1
2x + 3y = 2
When adding both equations we observe that:
Sentence 1: we have an equation of a variable, which in this case will be x. We can clear the value of x.
Sentence 2: Knowing the value of x, we can substitute in any equation and find the value of y.
Sentence 3: The value of x and y represents the point of intersection of both lines (x, y).
I’m gorilla da spinna RANGABANGIN ON MY CHEST
hi
x- 3/5 = 5x/ 6
6x - 18/5 = 5x
6x -5x = 18/5
x = 18/5
let's check : 18/5 - 3/5 = 15/5 = 3
5 * 18/5 / 6 = 18/6 = 3
result is correct.
The answers are 6i/13 and -6i/13. The work it attached below